Living tissue and organ donation by minors: Suggestions to improve the regulatory framework in Europe. (March 2016) - Van Assche, Kristof; Thys, Kristof; Vansweevelt, Thierry; Genicot, Gilles; Borry, Pascal; Sterckx, Sigrid
Whether living tissue and donation by minors is acceptable is the subject of considerable debate. In view of the vulnerable position of minors, the risks involved in the medical procedure, and the possible conflict of interests on the part of the parents, the legal approach in Europe has traditionally been very restrictive. However, this approach may raise concerns when a situation would arise where donation by a minor would still be in that person's best interests. Moreover, a very restrictive approach may be difficult to reconcile with the requirement to give due weight to the views of minors in accordance with their age and maturity. In the light of these considerations, this article examines whether there is room to improve the way in which living tissue and organ donation by minors is currently regulated across Europe. We first sketch the debate about the acceptability of using minors as living donors and explore its potential clinical need. Subsequently, we assess whether international legal instruments and guidelines offer any guidance to address the issues raised. This is followed by an analysis of the legal situation in the United States. Finally, we examine in detail the legal situation in Europe. To that aim, relevant regulations were compiled, translated, and analyzed in close cooperation with national legal experts. By way of conclusion, we compare the legal approach followed in the great majority of European countries with the one preferred in the United States and make suggestions to amend European transplant regulations to better protect the interests of minors.